Three-year incidence of elevated albuminuria and associated factors in a population-based cohort: The Taichung Community Health Study. (June 2015) - Liao, Li-Na; Liu, Chiu-Shong; Li, Chia-Ing; Lin, Wen-Yuan; Lin, Chih-Hsueh; Li, Tsai-Chung; Lin, Cheng-Chieh
Background: early-stage elevated albuminuria can be effectively detected by a spot urine albumin-to-creatinine ratio (UACR). Elevated albuminuria is a key predictor of diabetic nephropathy, progression to chronic kidney disease (CKD) or end-stage renal disease (ESRD), plus risk of cardiovascular disease (CVD) and mortality. Understanding these detectors may prevent future renal and cardiovascular disease. This study estimates three-year incidence in a representative sample of Taiwanese metropolitan adults to explore predictors. Methods: the Taichung Community Health Study (TCHS) is a representative sample of 2359 Chinese adults aged 40 years and over living in a metropolitan city during 2004–2005. In 2007–2009, a total of 1648 (71.3%) individuals participated in follow-up. This study includes only individuals with normal albumin excretion at baseline examination. Three-year incidence and baseline factors linked with elevated albuminuria were evaluated. Results: about 87.0% (n = 1434) of subjects exhibited normal albumin excretion at baseline. Three-year age- and gender-weighted incidence was 4.5% (95% CI: 3.4–5.6%). Multivariate logistic regression showed subjects with elevated waist-to-hip ratio (WHR) (OR: 2.2, 95% CI: 1.2–3.9), abnormal creatinine (OR: 3.7, 95% CI: 1.1–12.6), hyperuricaemia (OR: 1.8, 95% CI: 1.0–3.3) and elevated baseline UACR (OR: 4.0, 95% CI: 1.1–14.3 for UACR of 3.20–6.39 mg/g; OR: 16.7, 95% CI: 5.0–55.5 for UACR of 6.40–29.99 mg/g) were more likely to have elevated albuminuria. Conclusions: this is the first population-based longitudinal study to rate incidence of elevated albuminuria and identify associated factors in a random sample of a Chinese population. Central obesity, renal function, hyperuricaemia and baseline UACR are independent risk factors.